Effects of Rest Interval on Strength Recovery in Breast Cancer Survivors - Vieira, C. A.; Battaglini, C. L.; Ferreira-Junior, J. B.; Vieira, A.; Brito Vogt, M. F.; Freitas-Junior, R.; Oliveira, R. J.; Bottaro, M. (International Journal of Sports Medicine, 2015)
The purpose of this study was to compare the acute effect of 2 different resting intervals (RI) between sets of isokinetic knee extension exercise on peak torque (PT) and total work (TW) in breast cancer survivors (BCS) and control group (CNT). 16 BCS (52±4 years) and 14 CNT (53±6 years) performed 3 sets of 10 unilateral isokinetic knee extension repetitions at 60°.s− 1 on 2 separate days with 2 different RI between sets (1 and 2 min). There was a significant interaction between groups vs. exercise sets (p=0.03) and RI vs. exercise sets (p<0.001) for PT. PT was greater in CNT at 1st and 2nd sets compared to BCS group (CNT, 133.4±20.8 and BCS 107.6±19.9 Nm, p=0.012 and CNT, 118.9±19.6 and BCS, 97.1±15.9  Nm, p=0.045, respectively). The TW of the knee extensor was significant greater in CNT than BCS group for all 3 knee extension exercise sets. In conclusion, the present study suggests that Breast Cancer Survivors women may need a longer rest interval (longer than 2 min) to be able to fully recover during a 3 sets of isokinetic knee extension exercise training session.
Keywords: strength recovery; muscle fatigue; isokinetic